Pemikiran Ekonomi Karl Marx Menurut Konsep Ekonomi Islam - Singgih Muheramtohadi; Fita Nurotul Faizah (Universitas Cokroaminoto Yogyakarta, 2022)
The relation between Islam and Marxisme has been an interesting theme in Indonesia. In this country, Islam is the largest religion and there is inequality in economic field. In the academic level, so many students are interested in studying Marxism. There are many books attempeted to compare between Islam and Marx’s thought, by parallel comparison or by integration. In political Issues, many people emphasize the danger of the Marxism. This article aims to remap, so make the issues easier to understand them and to view the issues more balanced. This paper is narrated with analysis and description methods. The result of this study are, Islam has different basis, even both of them want the community without oppression. But Islam recognizes the potential differences of human being. And in Marx’s thought, the difference between people in accumulating wealthy lies in the mastery of the factors of production.